2022
DOI: 10.3390/atmos13111928
|View full text |Cite
|
Sign up to set email alerts
|

Footprints of COVID-19 on Pollution in Southern Spain

Abstract: Background: Many annual deaths in Spain could be avoided if pollution levels were reduced. Every year, several municipalities in the Community of Andalusia, located in southern Spain, exceed the acceptable levels of atmospheric pollution. In this sense, the evolution of primary air pollutants during the March–June 2020 lockdown can be taken as reliable evidence to analyze the effectiveness of potential air quality regulations. Data and Method: Using a multivariate linear regression model, this paper assesses t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 58 publications
0
2
1
Order By: Relevance
“…This increase in AOD during the lockdown period seems to be in contrast to the PM decrease reported by other authors for different locations in Spain [34,41,[49][50][51][52]. This discrepancy emphasises the differences between the behaviour shown by the aerosol near the ground measured by in situ techniques and the column aerosol, which is often driven by advected air masses travelling long distances.…”
Section: Discussioncontrasting
confidence: 78%
See 1 more Smart Citation
“…This increase in AOD during the lockdown period seems to be in contrast to the PM decrease reported by other authors for different locations in Spain [34,41,[49][50][51][52]. This discrepancy emphasises the differences between the behaviour shown by the aerosol near the ground measured by in situ techniques and the column aerosol, which is often driven by advected air masses travelling long distances.…”
Section: Discussioncontrasting
confidence: 78%
“…Therefore, several studies have also been conducted on the effects of the restrictions in this area. Most of them have focused on air quality in densely populated cities such as Barcelona [49], Madrid [50] or Valencia [51], in selected groups of cities [41,42] or in extensive networks with a large number of stations covering both urban and rural areas [52]. In general terms, all these in situ studies have reported a reduction in the PM recorded at ground level.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, there is a Port of 4.2·10 6 m 2 . Seaports have been reported to be a major source of PM due to the handling of materials, which causes the resuspension of loose materials ( Wirth et al, 2022 ). Indeed, the Port of Gijón moves a large quantity of bulk commodities (mainly coal, iron ore and cement), which are handled and stored in the open air, and thus, it can give rise to important diffuse emissions of particles due to the action of the wind.…”
Section: Methodsmentioning
confidence: 99%